Skaitļa simbolika Ļ.Tolstoja romānā "Karš un Miers" - Kučerenko, Oksana (Latvijas Universitāte, 2009)
Darbā pētīta skaitļu nozīme un simbolika Ļ. Tolstoja romānā „Karš un miers”. Pētījuma mērķis ir noskaidrot skaitļu simbolisko nozīmi minētajā daiļdarbā. Autors analizē romānā-epopejā minēto skaitļu nozīmi saistībā ar reliģisko un filozofisko skaitļu nozīmes traktējumu pasaules kultūras vēsturē. Īpaša uzmanība ir veltīta skaitļu „divi” un „trīs”, kā arī „septiņi” un „divpadsmit” simboliskajai nozīmei. Darbs sastāv no ievada, divām daļām un noslēguma. Pirmā daļa veltīta darba tēmas teorētiskajam problēmu apskatam, otrā – analītisks pētījums par romānā-epopejā biežāk minēto skaitļu simbolisko nozīmi. Pētījumu var izmantot filologi, kas nodarbojas ar līdzīgu problemātiku, kā arī lasītāji, kas interesējas par šādiem jautājumiem.

The present work is devoted to investigation of the meaning of numbers and their symbolic notions in epic novel „War and peace” by Leo Tolstoy. The aim of this research work is finding out of symbolic meaning of numbers in the above mentioned literary work. The author of the paper performs an analysis of numbers introduced into the narration of the epic novel in relation to religious and philosophic interpretation of the meaning of numbers in the history of human culture. Special attention is devoted to investigation of symbolic meaning of the following numbers: “two”, “three”, “seven” and “twelve”. The present work consists of an introduction, two chapters and a conclusion. The first chapter is devoted to general theoretical problems connected with the theme of the work; the second chapter presents an analytical investigation: the tasks put forward in the work concerning finding out of symbolism of the most frequently used numbers in the novel, are consequently realized in this chapter. The investigation can be used by philologists who are working in similar fields as well as by the readers who are interested in such kinds of issues.
Symbolics of Numbers in the Novel War and Peace by L. Tolstoy
Keywords: Krievu filoloģija